منهج الإمام البخاري رحمه الله في استنباط فقه السيرةمن كتابه الجامع الصحيح: Methodology of Imam Bukhari in deriving Fiqh ul Seerah in his book al-Jami al-Sahih - Dr. Ismail Muhammad Amin,; Ali Tariq, (Seerat Studies, 2023)
Al-Jami al-Sahih (usually referred as Sahih Bukhari ) of Imam Muhammad b. Ismail al-Bukhari is considered to be one of the authentic books of Hadith. Ulama and Scholars have been serving this book through their academic contributions and intellectual inputs . The Science of Studying the Seerah of the prophet (PBUH) with deep and analytic way and deriving the deep and applicable meanings and guidance from it is known as Fiqh ul Seerah. This article attempts to analyze methodology of Imam Bukhari in deriving Fiqh ul Seerah in his book al-Jami al-Sahih by selecting some Ahadith related to Creed, Worship, Transactional Matters, Ethics and Etiquettes. This work is a selective, model and thematic study of some of the Ahadith related to the topics mentioned above to analyze the methodology of Imam Bukhari in deriving the Fiqh ul Seerah in his book al-Jami al-Sahih and the methodology can further be extended to other themes and topics mentioned in al-Jami al-Sahih.